Adaptation, internalization and environmental damage - Lisandro Abrego; John Whalley (The University of Western Ontario, Department of Economics, 2002)
Existing literature ignores adaptation responses to external effects which, in turn, affect the design of appropriate internalization instruments. We use general equilibrium numerical simulation models based on OECD and UK data to analyze the significance of these responses to congestion externalities, and argue that they need to be taken into account in designing internalization instruments. We consider labor-leisure, regional labor mobility and house price responses to congestion externalities. Results show that not taking adaptation responses to environmental damage into account can seriously mislead analyzes of the consequences of internalizing externalities. If adaptation is present, externalities will be partially internalized, the gains from internalization will be smaller, and a simple internalization tax calculated as if adaptation were not present will typically overcorrect for the externality.
Keywords: H2; Q3; R4; R13; 330; Adaptation; Externalities; Congestion; Internalization; Migration